Ekosistem Moderasi Beragama dalam Pendidikan di Madura - Lailatul Mukarromah; Hadorotun Lailul Putri; Imron Ubaidillah (Institut Nurul Islam Mojokerto, 2025)
This study discusses the ecosystem of religious moderation in education in Madura, with a focus on the values of religious moderation applied in educational institutions, including Islamic boarding schools and formal schools. This ecosystem aims to create an inclusive, tolerant and harmonious educational environment amidst diversity of beliefs. This research uses a qualitative approach and literature analysis to explore how moderation values such as tolerance, justice, and nonviolence can be integrated into the educational curriculum. The research results show that Islamic boarding schools play a central role in forming moderate attitudes among students and the wider community. Apart from that, formal educational institutions are also starting to adopt the values of religious moderation in their teaching. This research recommends the need for collaboration between Islamic boarding schools and formal schools to strengthen the religious moderation ecosystem, as well as the importance of training for teachers to support the effective implementation of thes e values.